The Process of Democratization in Africa: The Case of Post Apartheid South African Democracy - Fufa, Fekede Sileshi (2018)
According to written sources, division among the races in South Africa can be traced back to the Dutch East Indian Company which colonized the area in the 17the century. The ethnic isolation increased during the years eventually resulting in apartheid rule beginning in the 1940’s. After the end of apartheid era, the post-apartheid government has largely been successful in ensuring that the citizens enjoyed freedom of speech, a just, free society and a transparent political system. This has been secured by the democratic constitution and the various acts and policies that were passes during post apartheid in the parliament of South Africa. Since 1994 with the end of apartheid system in South Africa different arrangements were happened. Among arrangements taken, implement various policies and acts aimed at ensuring that all citizens irrespective of race and colour as they enjoy with their rights in a unified, non-racist, non sexist in South Africa. The main aim of this paper is mainly examines the end of apartheid era and the birth of democracy in South Africa. As everyone know Africa continent is a place in which the leaders can do whatever they want. They do not follow the rule of law. Relatively, since 1994 these things were changed into democracy in South Africa. The paper is present to assess how could this democratic transition happened in South Africa. The paper has two parts. Part I provides survey of the post apartheid South African democracy and the apartheid era. Part II discusses the end of apartheid government and the birth of democracy in South Africa. Keywords: Apartheid, Racist, Birth, Afrikaners, Khoi-Khoi, San, Act, Mixe